A Refinement of the Formula for k-ary Trees and the Gould-Vandermonde’s Convolution - Chen, Ricky X. F. (The Electronic Journal of Combinatorics, 2008)
In this paper, we present an involution on some kind of colored k-ary trees which provides a combinatorial proof of a combinatorial sum involving the generalized Catalan numbers C_k,γ(n)=γk n+γk n+γn. From the combinatorial sum, we refine the formula for k-ary trees and obtain an implicit formula for the generating function of the generalized Catalan numbers which obviously implies a Vandermonde type convolution generalized by Gould. Furthermore, we also obtain a combinatorial sum involving a vector generalization of the Catalan numbers by an extension of our involution.